Biometric responses of third ratoon sugarcane varieties under variable water regime - Rodolfo Júnior, Francisco; Ribeiro Junior, Walter Quadros; Ramos, Maria Lucrécia Gerosa; Batista, Fábio Pedro da Silva; Lima, Cristiane Andréa de; Rocha, Omar Cruz (Comunicata Scientiae, 2018)
Water deficit is one of the main factors to limit sugar cane production. This paper’s goal is to characterize biometrically varieties of sugarcane under different water regimes. The experiment was performed using randomized design with three repetitions in parcels subdivided in time, in which three varieties: RB855156, RB835486 e RB867515 (plots), with absence and presence of irrigation (irrigated and rainfed - subplots) to which the plants were subjected, and data collection in six observations in time (50, 100, 150, 200, 250 and 300 days after cutting - DAC), were the subsubplots. The following biometrics were assessed: mean stem diameter (MSD), mean tiller height (MTH), number of green and completely open leaves (NoFOGL), length and width of +3 leaf (C+3 and L+3, respectively), leaf area index (LAI), leaf area (LA) and productivity. The data were subjected to variance analysis and regression at p<0.05. The variety RB867515 was the one that displayed higher MSD, MTH, C+3 and L+3 biometric values, both in irrigated cultivation and rainfed; it was observed that there was a decrease in NoFOGL values per tiller when the varieties were grown in rainfed conditions; the RB867515 variety had higher productivity, not differentiating to the RB855156, and proved better suited to water stress during the beginning of cultivation cycle.